PROBLEMS OF HYDROMETALLURGY ASSIMILATION IN THE REPUBLIC OF BELARUS (AS A MATTER FOR DISCUSSION) - O. S. Komarov (Литьë и металлургия)
The are examined the problems of development and mastery of hydrometallurgical technologies for processing of withdrawals containing metal for the purpose of the cult-ailment of their further accumulation and averting of environmental pollution.